2018
DOI: 10.1002/ccr3.1666
|View full text |Cite
|
Sign up to set email alerts
|

Safe delivery of lung stereotactic body radiation therapy in a patient with a left ventricular assist device and implantable cardioverter defibrillator

Abstract: Key Clinical MessageThis is the first case to discuss the safe delivery of stereotactic body radiation therapy to a left lower lobe lung nodule in a patient with a third generation left ventricular assist device (Heartware®) and implantable cardioverter defibrillator.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Previously, LVAD patients requiring radiation treatment for malignancy have received photon radiation, which has been demonstrated to be safe and effective. 2,3 To our knowledge, this is the first report of a patient with a HeartMate II and ICD who was treated with proton beam therapy.…”
Section: Discussionmentioning
confidence: 86%
“…Previously, LVAD patients requiring radiation treatment for malignancy have received photon radiation, which has been demonstrated to be safe and effective. 2,3 To our knowledge, this is the first report of a patient with a HeartMate II and ICD who was treated with proton beam therapy.…”
Section: Discussionmentioning
confidence: 86%
“…Multiple case studies have reported on patients with LVADs receiving external beam radiation. [6][7][8][9][10][11][12][13][14][15] All these studies looked at directed radiation, with none involving a patient receiving TBI or LVAD controller dose. Directly comparing techniques and dose estimates is challenging.…”
Section: Discussionmentioning
confidence: 99%
“…While the effect of radiation on other cardiac implantable electrical devices (CIEDs), including pacemakers and defibrillators, has been well studied, there remains limited data on radiation to LVAD 3–7 . Much of the existing radiation data is in the form of in‐vitro studies and case reports 8–15 . None of these studies considered the radiation sensitivity of the LVAD external controller.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned in the reports, when a patient's disease was too advanced for surgery or if the patient presented with metastasis, alternative options such as chemotherapy, radiotherapy or palliative care were chosen (20,21,28). The effects of radiation on CF-LVADs were discussed by Emerson et al and Ostertag et al (29,30) who suggested that the rotor and rotor magnets within the CF-LVAD were of particular concern in patients receiving radiation. Recommendations for CF-LVAD protection during radiotherapy include protecting the CF-LVAD battery source by placing it outside the RT field.…”
Section: Discussionmentioning
confidence: 99%